Heat Balance When Climbing Mount Everest - Szymczak, Robert K.; Błażejczyk, Krzysztof (Frontiers in Physiology, 2021)
(1) Background: Mountaineers must control and regulate their thermal comfort and heat balance to survive the rigors of high altitude environment. High altitudes feature low air pressure and temperatures, strong winds and intense solar radiation, key factors affecting an expedition’s success. All these climatic elements stress human heat balance and survival. We assess components of human heat balance while climbing Mt. Everest. (2) Material and Methods: We calculated climbers’ heat balance using the Man-ENvironment heat EXchange model (MENEX-2005) and derived meteorological data from the National Geographic Expedition’s in situ dataset. Three weather stations sited between 3810 and 7945 m a.s.l. provided data with hourly resolution. We used data for summer (1 May–15 August 2019) and winter (16 October 2019–6 January 2020) seasons to analyze heat balance elements of convection, evaporation, respiration and radiation (solar and thermal). (3) Results Meteorological and other factors affecting physiology—such as clothing insulation of 3.5–5.5 clo and activity levels of 3–5 MET—regulate human heat balance. Elevation above sea level is the main element affecting heat balance. In summer two to three times more solar radiation can be absorbed at the summit of the mountain than at the foot. Low air pressure reduces air density, which reduces convective heat loss at high altitude by up to half of the loss at lower locations with the same wind speed and air temperature. (4) Conclusions: 1. Alpinists face little risk of overheating or overcooling while actively climbing Mt. Everest, despite the potential risk of overcooling at extreme altitudes on Mt. Everest in winter. 2. Convection and evaporation are responsible for most of the heat lost at altitude. 3. Levels of physical activity and clothing insulation play the greatest role in counteracting heat loss at high altitude.